Educação Hoje: a magazine for High School in Brazil in the 1960s - Revah, Daniel (2016)
This study aims to analyze the reading model and teacher training contained in Educação Hoje, published by Brasiliense (1969 - 1971). The magazine supported the circulation of some educational practices carried by experimental High Schools organized between 1950 and 1970. The analysis is carried out in the perspective of the cultural history, with emphasis on the description and analysis of editorial formula. Also, it was analyzed the first article, in the inaugural issue, especially its relationship between editorial formula of the whole publication and the principles expressed in its editorial, but also taking it as an example of a source of High School pedagogical practices promoted by this publication, in the most repressive period of military dictatorship.